Flexural strength of span steel-reinforced concrete truss composite structures - Galinska, Tatiana; Ovsii, Dmytro; Ovsii, Oleksandra (Academic journal Industrial Machine Building Civil Engineering, 2020)
The scientific article proposes a method for calculating the bending strength of steel-reinforced concrete (SRC) composite span truss structures. This method allows calculating the flexural strength of the calculated sections of steel-reinforced concrete truss structures, taking into account their stress-strain state at the time of maximum load-bearing capacity or failure. The analysis of experimental and theoretical values of flexural SRC truss beam strength showed their adequate convergence, which allows the application of the calculation method in practice design SRC  span truss structures and members.
Keywords: steel-reinforced; concrete; span; composite; truss structures; flexural strength